2013
DOI: 10.7314/apjcp.2013.14.6.3925
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 (Ile462Val), CYP1B1 (Ala119Ser and Val432Leu), GSTM1 (null), and GSTT1 (null) Polymorphisms and Bladder Cancer Risk in a Turkish Population

Abstract: We aimed to investigate bladder cancer risk with reference to polymorphic variants of cytochrome p450 (CYP) 1A1, CYP1B1, glutathione S-transferase (GST) M1, and GSTT1 genes in a case control study. Polymorphisms were examined in 114 bladder cancer patients and 114 age and sex-matched cancer-free subjects. Genotypes were determined using allele specific PCR for CYP1A1 and CYP1B1 genes, and by multiplex PCR and melting curve analysis for GSTM1 and GSTT1 genes. Our results revealed a statistically significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…CYP1A1*2B A/G (I1e462Val) and Bladder Cancer Risk: As established above, six studies, with a total of 908 cases and 815 controls, evaluated the association of BC risk in I1e462Val A/G mutation Fontana et al, 2009;Grando et al, 2009;Ozturk et al, 2011;Berber et al, 2013;Fu et al, 2013). According to our results, no significant association between this polymorphism and BC risk was found in all genetic models in the overall populations: i) G vs. A (OR = 1.04, 95% CI = 0.74-1.47, P = 0.810); ii) GG vs. AA (OR = 1.47, 95% CI = 0.70-3.07, P = 0.308); iii) AG vs. AA (OR = 0.97, 95% CI = 0.74-1.27, P = 0.819); iv) GG+AG vs. AA (OR = 1.01, 95% CI = 0.68-1.48, P = 0.970); v) GG vs. AG+AA (OR = 1.45, 95% CI = 0.70-3.02, P = 0.317).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP1A1*2B A/G (I1e462Val) and Bladder Cancer Risk: As established above, six studies, with a total of 908 cases and 815 controls, evaluated the association of BC risk in I1e462Val A/G mutation Fontana et al, 2009;Grando et al, 2009;Ozturk et al, 2011;Berber et al, 2013;Fu et al, 2013). According to our results, no significant association between this polymorphism and BC risk was found in all genetic models in the overall populations: i) G vs. A (OR = 1.04, 95% CI = 0.74-1.47, P = 0.810); ii) GG vs. AA (OR = 1.47, 95% CI = 0.70-3.07, P = 0.308); iii) AG vs. AA (OR = 0.97, 95% CI = 0.74-1.27, P = 0.819); iv) GG+AG vs. AA (OR = 1.01, 95% CI = 0.68-1.48, P = 0.970); v) GG vs. AG+AA (OR = 1.45, 95% CI = 0.70-3.02, P = 0.317).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Manual search of the reference lists did not reveal any additional eligible studies. Thus, eight relevant studies focused on two of the most studied polymorphisms in CYP1A1 (CYP1A1*2B A/G (I1e462Val) and CYP1A1*2A T/C (MspI) and risk of BC were included in our meta-analysis Li et al, 2007;Srivastava et al, 2008;Grando et al, 2009;Fontana et al, 2009;Ozturk et al, 2011;Fu et al, 2013;Berber et al, 2013). Of these, the study by Brockmöller et al identified the relationship between CYP1A1 polymorphisms and BC risk in both alleles, and were therefore treated independently.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…is one of the major environmental risk factors for breast cancer due to the presence of procarcinogens in tobacco (Berber et al, 2013). In our study most of the workers rolling beedi for more than 10 years and they affected with different types of health issues like headache, back pain, urinary infection, leg pain, shoulder pain, low eye contact, blood pressure, skin allergy.…”
Section: Introductionmentioning
confidence: 81%
“…From the molecular point of view, evidence in the literature supports the existence of distinct pathogenetic pathways involved in bladder cancer development (Berber et al, 2013). By departing from this fact, we have proposed the hypothesis that the prognosis of bladder cancer may be worse in the presence of cancers associated with smoking and pathological stage especially if the histological grade is high.…”
Section: Discussionmentioning
confidence: 96%